Intervention of Intellectual Property Rights on Household Industry Productivity - Yulianty Jacob, Yossie Maria; Tungga, Ishak Alfred; Peku Wali, Umbu Lily (Faculty of Law, Universitas Jenderal Soedirman, 2019)
All seaweed farmer groups can naturally train their members. Even local governments have provided services for increasing the productivity of home industry of seaweed farmers as regional superior products, but there has been no IPR intervention action on superior products in order to provide protection and encourage the type of seaweed processing business to obtain IPR. Research uses this normative and empirical legal research. This means that legal material data is used in reviewing and tracing various rules regarding IPR in the productivity of Industrial Seaweed RT in Rote Ndao Regency. Research shows that branded processed seaweed food products are fostered and developed by local governments, but IPR intervention is not carried out by regional governments to protect and encourage each type of product to develop regional superior products. The legal impact on unbranded seaweed food products in Rote Ndao District is that the community does not yet feel secure by not having IPR from the types of products available.Keywords: IPR Intervention, Industrial Productivity RT, Seaweed